2014
DOI: 10.1093/europace/euu050
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contractility modulation: first experience in heart failure patients with reduced ejection fraction and permanent atrial fibrillation

Abstract: CCM signal delivery is feasible in HF patients with permanent AF by sequential atrial-ventricular pacing, so that the atrial pacing spike is interpreted as a p wave by the CCM signal delivery algorithm. This experimental approach can be considered in individual cases. A new CCM algorithm, which does not require an atrial electrode, is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…The experience to-date includes patients with NYHA classes II, III and IV symptoms, mostly with narrow QRS, but some also with wide QRS, after being treated by CRT. At present, the device can deliver the therapy to patients that are not in permanent atrial fibrillation, even though a preliminary experience with permanent AF was published recently showing the feasibility and clinical benefit in that population as well [14].…”
Section: Discussionmentioning
confidence: 99%
“…The experience to-date includes patients with NYHA classes II, III and IV symptoms, mostly with narrow QRS, but some also with wide QRS, after being treated by CRT. At present, the device can deliver the therapy to patients that are not in permanent atrial fibrillation, even though a preliminary experience with permanent AF was published recently showing the feasibility and clinical benefit in that population as well [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although permanent atrial fibrillation prevents the optimizer stimulus due to loss of the atrial sensing, current versions of the device can overcome this limitation, allowing effective impulse delivery in the presence of atrial fibrillation. Early experience with this novel algorithm (linked to the presence of a CRT device impulse) was published by Roger et al [61]. who described use of CCM in 5 patients who developed permanent atrial fibrillation at or after optimizer implantation.…”
Section: Device Therapy For Heart Failurementioning
confidence: 99%
“…The new‐generation Optimizer, the Optimizer Smart, includes an algorithm that does not require the implantation of an atrial lead (keeping the 2 ventricular leads only), thereby further simplifying the implantation procedure. The new mode also allows the delivery of CCM therapy in patients with permanent atrial fibrillation, which was considered a contraindication for the prior‐generation Optimizer device . In a recent study, it was demonstrated that efficacy and safety of CCM were similar when the signal was delivered through either 1 or 2 ventricular leads .…”
Section: Discussionmentioning
confidence: 99%
“…The new mode also allows the delivery of CCM therapy in patients with permanent atrial fibrillation, which was considered a contraindication for the prior-generation Optimizer device. 21 In a recent study, it was demonstrated that efficacy and safety of CCM were similar when the signal was delivered through either 1 or 2 ventricular leads. 22 These results support the potential future use of a single ventricular lead for delivery of CCM, further reducing device implantation-associated risk.…”
Section: Discussionmentioning
confidence: 99%